Quantitative Determination of Subnanomolar Concentration of Nitrite in Natural Water by High-Performance Liquid Chromatography. - ABU-SHAMMALA., FARID (Asian Journal of Chemistry, 2010)
A new chromatographic method is presented that successfully determines nirite in natural water at subnanomolar concentration. The procedure was based on converting the nitrite to a derivative using 2,4- dinitro phenyl hydrazine followed by separation using High-Performance Liquid Chromatography (HPLC). The method is simple, rapid, and requires minimal sample preparation. The 2,4-dinitro phenyl azide formed is stable for at least 5 weeks under cold and dark conditions. The accuracy of the method was checked using the standard colorimetric technique in several natural water types. The detection limits of nitrite in three types of natural water were found to range from 0.1 to 0.2, with relative standard deviations for the complete procedure varying between 4 and 8%. The method has recovery range from 95 to 100% with relative standard deviations between 2 and 5%. Applications of the HPLC method to study the speciation of nitrite in natural waters in Gaza Strip are also presented.